Closed-type wing for drones: positive and negative characteristics - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The paper presents the aerodynamics of a wing of a closed oval ellipsoidal shape, designed with the use of the molecular-kinetic theory. The positive and negative characteristics of aircraft - drones with an oval wing are described. The theoretical calculations have been experimentally checked.
Keywords: oval wing; drones; Aerodynamics